Proyecto asociativo para la creación de una planta productora de abono orgánico en base al reciclaje de los desechos del mercado de Conocoto y su distribución a través de un punto de venta en la parroquia Conocoto - Rueda Guerrero, Franz Alberto (2015)
Composting is a technique that has been practiced for thousands of years, their evolution over time is due mostly to the Eastern peoples and their success was to combine scientific knowledge with traditional peasant. Start knowing a little of its history, the environment in which developed and the importance of taking this technique in the pursuit of environmental conservation. The problem of disposal of waste generated by the markets of major cities was not having a correct treatment, as they are deposited in open dumps that cause negative impacts to the environment. For this reason we have entered the process of analysis to create a plant producing organic fertilizer using waste generated by the market Parish Conocoto through composting method that can treat rationally organic waste and conserve nutrients found in these wastes and use them in agriculture, as the main function of composting is to fertilize the soil to add nutrients to the original soil